Failure of empire: Valens and the Roman state in the fourth century A.D - Lenski, Noel Emmanuel (The transformation of the classical heritage, 2002)
The Pannonian Emperors -- The revolt of Procopius -- Valens's first Gothic War -- Valens and the eastern frontier -- Religion under the Valentiniani -- Administration and finance under Valentinian and Valens -- The disaster at Adrianople.